Volcanogenic cherts in the late Precambrian Conception Group, Avalon Peninsula, Newfoundland - Hughes, Charles J. (Canadian Journal of Earth Sciences, 1976)
Bedded rocks of cherty appearance are locally abundant and conspicuous in the late Precambrian Conception Group of the Avalon Peninsula, southeast Newfoundland. Structural, petrographical, and chemical data from a well exposed locality near St. John's indicate that these beds are tuffaceous, predominantly of acid vitric composition, formed by pyroclastic material derived from contemporaneously active subaerial volcanic sources accumulating in sea water, and subjected to submarine transport. Appreciable quantities of acid material were thus erupted in 'Conception time.'